PK study of octreotide based on LC–MS/MS combining protein precipitation and impurity extraction technique. (April 2015) - Wang, Qian; Liang, Yan; Rao, Tai; Xie, Lin; Ye, Wei; Fu, Hanxu; Zhou, Lijun; Xing, Rong; Shao, Yuhao; Xiao, Jingcheng; Kang, Dian; Wang, Guangji
Aim: To establish a robust methodology for quantitative analysis of therapeutic peptide in biological samples.Materials & Methods: Octreotide was chosen as a model therapeutic peptide, and oxidized-octreotide was synthesized as internal standard. Protein precipitation combining liquid-liquid extraction technique was adopted to enhance the recovery and reduce the endogenous interferences effectively. A LC–MS/MS method for the quantification of octreotide in plasma has been optimized and validated according to FDA guidelines.Results: Linearity, selectivity, accuracy, precision, stability, matrix effect and recovery were within bioanalytical method validation acceptance criteria as FDA guidelines. The methodology was then successfully applied into the studies for octreotide.Conclusion: This robust methodology would be useful for the PK studies for octreotide and other therapeutic peptides.